SURVEI POLA PEMBINAAN SEKOLAH SEPAKBOLA DI KABUPATEN BATANG (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the pattern of extracurricular school sports coaching in high schools in Salatiga . This study is a qualitative research approach of naturalistic descriptive analysis , while the data collection methods used by the researchers are observation , interviews , and documentation . The population used in this research that all high schools in Salatiga conducting extracurricular sports activities consisting of SMA N 1 Salatiga , Salatiga SMA N 2 , N 3 Salatiga SMA , SMA Muhammadiyah Salatiga , Salatiga 1 Christian High School , Christian High School 2 Salatiga , Satya Discourse and Christian high School . Respondents in this study were interviews of principals, waka student non-academic and extracurricular coaches at high schools in Salatiga . The results of research on patterns of extracurricular sports coaching such as: Human Resources trainer is 87.5 % with a total of 193 athletes . From the research it can be concluded that , patterns coaching conducted by the school in Salatiga City high schools for extracurricular sports is good enough . It's just a lot of factors that make all the coaching not run optimally , such as a mismatch between the talent and interests of learners, condition of facilities and good infrastructure inadequate.